Development of active control within working memory: Active retrieval versus monitoring in children. (May 2014) - Blain-Brière, Bénédicte; Bouchard, Caroline; Bigras, Nathalie; Cadoret, Geneviève
This study aimed to compare children's performance on two mnemonic functions that engage the lateral prefrontal cortex. Brain imaging studies in adults have shown that the mid-ventrolateral prefrontal cortex is specifically involved in active controlled retrieval, and the mid-dorsolateral prefrontal cortex is specifically involved in monitoring mnemonic information (Petrides, 2005). Eighty-two children aged from 6 years, 8 months to 8 years, 7 months were tested. They showed equivalent success rates in active retrieval and monitoring with color and shape information. However, children were slower in monitoring than in active retrieval in color trials. The results demonstrate that the specialized contributions of the lateral prefrontal cortex emerge conjointly during childhood giving children multiple tools to exert an active control within memory.